1977
DOI: 10.1037/0022-0663.69.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence in the classroom: A field study.

Abstract: A field study was conducted in which fifth-grade students spent three class periods per week for 6 weeks in small interdependent learning groups. Each student taught the other members of his or her group a portion (IIn) of the assignment. These students were compared with fifth graders in traditional, teacher-taught (control) classrooms. As hypothesized, students in the interdependent learning groups (experimentals) manifested higher self-esteem than controls and liked groupmates more than other classmates. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(51 citation statements)
references
References 18 publications
2
47
0
2
Order By: Relevance
“…Desforges, Lord, Ramsey, Mason, Van Leeuwen, West, & Lepper, 1991;Desforges, Lord, Pugh, & Sia, 1997;Hewstone & Brown, 1986;Van Oudenhoven, Groenewoud, & Hewstone, 1996;Wilder, 1984), others have only found speci®c attitude change without a corresponding generalization effect (e.g. Blaney, Stephan, Rosen®eld, Aronson, & Sikes, 1977;Johnson & Johnson, 1981;Slavin, 1979). Studies that measure attitudes toward the out-group as an abstract social category often fail to obtain any generalization effect (Bond, DiCandia, & MacKinnon, 1988;Wilder & Thompson, 1980;Weigel, Wiser, & Cook, 1975).…”
Section: Generalization Of Reduced Intergroup Biasmentioning
confidence: 95%
“…Desforges, Lord, Ramsey, Mason, Van Leeuwen, West, & Lepper, 1991;Desforges, Lord, Pugh, & Sia, 1997;Hewstone & Brown, 1986;Van Oudenhoven, Groenewoud, & Hewstone, 1996;Wilder, 1984), others have only found speci®c attitude change without a corresponding generalization effect (e.g. Blaney, Stephan, Rosen®eld, Aronson, & Sikes, 1977;Johnson & Johnson, 1981;Slavin, 1979). Studies that measure attitudes toward the out-group as an abstract social category often fail to obtain any generalization effect (Bond, DiCandia, & MacKinnon, 1988;Wilder & Thompson, 1980;Weigel, Wiser, & Cook, 1975).…”
Section: Generalization Of Reduced Intergroup Biasmentioning
confidence: 95%
“…Two of these empirical studies of Jigsaw concluded with negative findings (Moskowitz, Malvin, Schaeffer, & Schaps, 1983;Moskowitz, Malvin, Schaeffer, & Schaps, 1985). The remaining four papers concluded with favourable effects on social relations (Blaney, Stephan, Rosenfield, Aronson, & Sikes, 1977;Bridgeman, 1981;Rego & Moledo, 2005;Walker & Crogan, 1998). However, studies claiming to find favourable effects on intergroup relations have methodological limitations.…”
Section: Introductionmentioning
confidence: 91%
“…For instance, a study using attitudes towards class members as outcome variable (Blaney et al, 1977) is repeatedly, but incorrectly, referred to when arguing for Jigsaw's effectiveness for improving outgroup attitudes (assuming a generalization beyond class members). Another study (Walker & Crogan, 1998) contrasted one Jigsaw class that had two teachers with a non-interdependent cooperative class, in which the researchers identified a negative development.…”
Section: Are Cooperative Groups Effective To Improve Intergroup Relatmentioning
confidence: 98%
See 1 more Smart Citation
“…Although it is common to study interdependence using qualitative methods, given the large group of respondents a survey was deemed more feasible. Moreover, such an approach has been successfully used before in student interdependence studies (Blaney, Stephan, Rosenfield, Aronson, & Sikes, 1977). To measure the networks, a network survey was used, as is common in network research (Scott & Carrington, 2011).…”
Section: Procedures and Participantsmentioning
confidence: 99%